Screening of Serum Alkaline Phosphatase and Phosphate Helps Early Detection of Metabolic Bone Disease in Extremely Low Birth Weight Infants - Zhang, Hui; Jia, Qiong; Piao, Meihua; Chang, Yanmei; Zhang, Jinghui; Tong, Xiaomei; Han, Tongyan (Frontiers in Pediatrics, 2021)
Background: Extremely low birth weight (ELBW, < 1000 g) infants have high risk of metabolic bone disease (MBD). Due to the late appearance of radiological signs, diagnosis of MBD in ELBW infants might be delayed and its prevalence underestimated in this group of patients. This study adopted serial screening of serum alkaline phosphatase (ALP) and phosphate (P) of ELBW infants to determine whether such screening is helpful for the early detection of MBD. Materials and Methods : We performed a retrospective study of the preterm infants with a gestational age ≤ 31 weeks and birth weight < 1000 g. According to their serum ALP and P levels, MBD was diagnosed and graded, and divided into non-MBD, mild and severe; the diagnosed cases of MBD were divided into early MBD (≤ 4 weeks after birth) and late MBD (> 4 weeks after birth) according to the time of onset. Results : A total of 142 ELBW infants were included, with a median gestational age of 28.1 (26.5-29.7) weeks and a median birth weight of 875 (818-950) g. 73 cases of MBD were diagnosed, and the total prevalence was 51.4% (mild MBD, 10.6%; and severe MBD, 40.8%). Male infants, breastfeeding and sepsis would increase the risk of severe MBD. Most MBD in ELBW infants occurred at 3-4 weeks after birth. 62% (45/73) of infants were diagnosed as having early MBD, which are diagnosed earlier than late MBD ([24(21-26)] vs. [39(36-41)], t=-7.161, P<0.001). Male sex (OR 2.86, 95%CI 1.07-7.64, P = 0.036), initial high ALP levels(OR 1.02, 95%CI 1.01-1.03, P < 0.001) , and breastfeeding (OR 5.97, 95%CI 1.01-25.12, P = 0.049) are independent risk factors for the development of early MBD. Conclusion : The risk of MBD among ELBW infants is very high. Most cases occurred early and were severe. Male infants, initial high ALP levels and breastfeeding are closely related to the increased risk of early MBD. Serial screening of serum ALP and P helps early detection of MBD; it is recommended to start biochemical screening for ELBW infants 2 weeks after birth and monitor their biochemical markers weekly.